Autocuidado a luz da teoria de dorothea orem: panorama da produção científica brasileira - Silva, Karem Poliana Santos da (Brasil, 2023)
Objective: To describe the panorama of scientific production on Self-Care in the Light of Dorothea Orem's Theory in several publications on the subject. Methods: This is a bibliometric, quantitative, descriptive study in the scientific literature. In the search, the descriptors “Theory ofself-care and Dorothea Orem” were used in the LILACS, SCIELO, and BDENF databases. The data obtained were analyzed using the Excel spreadsheet. Results: Of the 74 articles analyzed, it was observed that research on the Theory of Self Care has grown and had greater visibility since the 2000s. Highlighting the Northeast region with a higher percentage of articles published on the subject. The authors opted for a qualitative methodological design where most of these studies were published in the Revista Brasileira de Enfermagem. Conclusion: Dorothea Orem's theory in Brazilian scientific production encompasses extensive knowledge that allows to consolidate and enriches the nursing process. The knowledge of this theory allows identifying the needs of self-care, establishing solutions for the individual, and enabling him to develop his care. In this sense, the appropriation of this theory is important for the teaching, practice, and development of science in nursing.